An evaluation of Nirachara-college project using CIPP model - Pongrangsarn, Phattharamanat; Suwannakeeree, Wongduan; Klankhajhon, Sirikanok; Songthai, Nichakarn; Yunak, Ratanachadawan (NU Journal of Nursing and Health Sciences, 2020)
The purpose of this cross-sectional descriptive survey was to evaluate the Nirachara college project of Pa Sao Municipality, Mueang District, Uttaradit Province by using the CIPP model in 4 aspects which are context, input, process and product. Data were collected from 36 workers of Nirachara college project, 45 elderly students who are current students, and 29 elders who graduated from the project by using 3 sets of questionnaire developed by the researchers; for workers, current students and graduates. Content validity was checked by 3 experts and tested for reliability with Cronbach's alpha coefficient were .97, .92 and .80 respectively. Statistics used for data analysis were frequency, percentage, mean and standard deviation The results indicated that the overall of context evaluation is consistency with the policies and problems of elderly at a high level ( = 4.20, S.D. = .61), input evaluation including resource adequacy and plan is at a high level ( = 3.83, S.D. = .54), process evaluation include implementing the plan and adjusting the plan is at high level ( = 4.00, S.D. = .49), and product evaluation as the characteristics of graduates according to the objectives of the curriculum is at a high level ( = 3.98, S.D. = .65). Using the CIPP model to evaluate the Nirachara-college project provides useful information for executives to make improvements in the project operations for developing the quality of life of the elderly in Pa Sao Municipality, Pa Sao District, Uttaradit Province. It is also the information to disseminate and expand the establishment of the elderly school project to other local administrative organizations.